Perceived Statistics Self-Efficacy, Research Anxiety, and Research Confidence of Mathematics Pre-Service Teachers in One State University in the Philippines - Romero, Ericka Paula Jane Capistrano; Laguerta, Marjorie Mendoza; Andrade, Rose Reyes (Jurnal Pendidikan Progresif, 2023)
Perceived Statistics Self-Efficacy, Research Anxiety and Research Confidence of Mathematics Pre-Service Teachers in One State University in the Philippines. Objectives: This study aimed to investigate the relationship between statistics self-efficacy, research anxiety and research confidence. This research also determined whether statistics self-efficacy can predict research confidence. Methods: Purposive sampling method was used among 71 students who had previously taken statistics and research employing adapted questionnaires in data collection. Findings: Results revealed that statistics self-efficacy and research anxiety have a relationship with motivated behavior and statistical theory. Meanwhile, statistics self-efficacy and research confidence were found to be associated in terms of lecture behavior, use of information technology, motivated behavior, time management, and statistical theory. Furthermore, this study discovered that statistical theory and time management could predict respondents' research confidence. Conclusion: The findings imply that improving the statistics self-efficacy of prospective mathematics teachers is indispensable for mathematics research production. Keywords: mathematics, pre-service teachers, research anxiety, research confidence, statistics self-efficacy.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202343